Pengaruh Penggunaan Metode Demonstrasi, Diskusi dan Motivasi Belajar terhadap Prestasi Belajar Siswa pada Mata Pelajaran Matematika di Kelas XI IPA MAN I Kota Mojokerto - Hanik Masruroh (PROGRESSA: Journal of Islamic Religious Instruction, 2017)
Teaching and learning activities are activities carried out consciously and purposefully. Therefore, so that the activity can run well and achieve the expected goals, it must be done with the right learning strategy or approach. The objectives of this study are: 1) Describe the influence of the use of demonstration methods on chemistry learning outcomes in Class XI IPA MAN I City of Mojokerto. 2) Describe the influence of Discussion on the learning outcomes of chemistry in the Class XI Science MAN I Kota Mojokerto 3) Describe the effect of learning motivation on the learning outcomes of chemistry in the Class XI Science of MAN I in Mojokerto City 4) Describe the relationship Using the demonstration method, Learning Discussion and Motivation towards learning outcomes chemistry in Class XI IPA MAN I City of Mojokerto. From the results of the analysis it can be concluded as follows: 1) Test t on the variable Using the demonstration method (X1) obtained Regression coefficient (B) 0.104 (10.4%), tcount 2.127 with significance t of 0.047 Because the significance t is less than 5% (0.047 <0.05), then the null hypothesis (H0) is rejected and the work hypothesis (Hi) is accepted. The t test for the Discussion variable (X2) obtained Regression coefficient (B) 0.140 (14.0%), tcounted at 0.407 with a significance t of 0.009. Because the significance of t is smaller than 5% (0.009 <0.05), the Zero Hypothesis (H0) is rejected and the working Hypothesis (Hi) is accepted. T test for Motivation learning variable (X3) obtained Regression coefficient (B) 0.202 (20.2%), tcount equal to 0.006 with significance t of 0.005. Because the significance of t is smaller than 5% (0.005 <0.05), the null hypothesis (H0) is rejected and the work hypothesis (Hi) is accepted. Whereas the different tests with the Independent Samples Test state that there are differences in learning achievement taught using the demonstration method with discussions with a t value of 0.336 with a significant level of 0.008 and 0.008 <0.05, so that Zero (H0) is rejected and the work hypothesis (Hi) is accepted. So that either through partial testing or different tests with the Independent Samples Test shows there are differences. 2) The difference in learning achievement between students who have high learning motivation contributes 1,000 (100%) and a low one with 0.614 (61.4%). So: There is a difference in learning achievement between students who have high and low learning motivation in class XI IPA MAN I Mojokerto City. 3) From the calculation results, the calculated F value is 2388,512 (significance F = 0,000). So Fcount> Ftable (2388,512> 2.03) or Sig F <5% (0,000 <0,05). This means that together the independent variables consist of variables using the demonstration method (X1), Discussion (X2), Motivation to learn (X3) has a simultaneous effect on the variables of student achievement on Mathematics (Y)